Immigration and the national character - McDonald, Ethel (My University, 1907)
Introduction: Immigration is the life history of the countries of the new world. It is through this process that European civilization has spread until now it covers the globe. It is only recently that the immigration problem has assumed a serious aspect. All through the middle ages there was very little migration. The history of the migratory movement to the United States begins with the first settlement at Plymouth. In one sense all the inhabitants of the United States are immigrants, the only exception being the Indians. But this is a very misleading conception. There is a great difference between those who took part in building a political commonwealth by their toil and sacrifice and those who simply migrate to a country where laws and customs are already fixed, and a national existence certain. The former are called the colonists and the latter the immigrants. The number of people here at the beginning of the Revolutionary War is not accurately known. The population of New England was produced from an immigration of 20,000 persons, who arrived before 1640. These people spread to other colonies without receiving an additional increase from them. Franklin stated in 1751 that the population then amounting to about one million had been produced from an immigration of less than 80,000. The first census of the United States in 1790, gave the total population as 3,924,214, but this number did not include Vermont and the territory northwest of the Ohio River, which, one authority claims, would make the total over 4,000,000. The first records of immigration begin with the year 1820. The number of persons migrating to this country after the Revolutionary War to 1820, although not knowm, is estimated by good authorities at 250,000...
Citation: McDonald, Ethel. Immigration and the national character. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Migration; Migration in the United States; American History; Melting Pot; Theses